Prevalence of medication-induced delirium in older people admitted to intensive critical unit: a systematic review - Bruno DA SILVA; Ivis MARTINS; Beatriz HATA; Marcia DOS SANTOS; Priscila PACKEISER; Marilia CAMPOS; João Paulo RODRIGUES; Maria Teresa HERDEIRO; Fátima ROQUE; Helaine CAPUCHO; Maria Olívia ZANETTI; Júlia RASO; et al. (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: to estimate the prevalence of medication-induced delirium and drug-related problems (DRP) in older people hospitalized in intensive care unit (ICU). Methods: A systematic review were conducted in PubMed, EMBASE, LILACS, Ageline, Web of Science, and Cochrane databases (until March 2023). Clinical trials and observational studies that investigated the contribution of medication in the occurrence of delirium and compared with critically ill older patients (aged≥65 years old) without the syndrome were included. We excluded emergency departments, medical wards, primary and secondary healthcare levels, patients with delirium tremens; metabolic encephalopathy; dementia; palliative care; and brain metastasis. The references were entered into Rayyan QCRI. Two pairs of reviewers selected the articles, extracted data, and assessed the risk of bias (ROBINS-I). Results: Of 12,492 studies retrieved, after de-duplication exclusion (n=6,025), title/abstract (n=6,467) and full reading (n=286), two met the inclusion criteria. Both were observational (cohort), developed in high-income countries, with high level of risk of bias (overall). The frequency of delirium and subsyndromal delirium was 15.8% to 33.9%. Independent risk factors were the exposure of opioids and use of corticosteroids. Delirium increased the length of hospital stay in ICU, and the mechanical ventilation. Conclusion: Further studies are necessary to understand the DRP and characteristics of pharmacotherapy associated with delirium in critically ill older people. Adverse drug reactions and deliriogenic load seem to contribute to the occurrence of syndrome.